Application of PBL with ESD Context in Improving Learning Outcomes and Sustainability Awareness of Learners - Farida Agustina Damayanti; Jun Surjanti (Buana Pendidikan, 2022)
The aim of this study is to realized an application of PBL with ESD context in improving learning outcomes and sustainability awareness of class X learners at Labschool Unesa 1 Secondary School. The design of the study is to use quasi-experiments with pre-post test types of research. The results showed that there was a significant difference in the learning outcomes of learners after the application of the model. Based on the results of the t test statistics, the value F calculates 1.492 with a value of p 0.000 < 0.05 which means Ho is rejected or hypothesis zero is rejected while the alternative hypothesis is accepted. Then there are differences in the learning outcomes of conventional model groups with ESD context PBL groups. This difference is reinforced by the data on the acquisition of the mean of each group, where for the experimental group (ESD context PBL model) obtained a mean result of 89.60. While the control group (conventional model) obtained a mean result of 78.00. Formed on the aftereffect of the examination that the experimental group (ESD context PBL model) obtained higher results than the control group (conventional model) with a significant difference of 11.6. Then for the sustainability awareness profile of learners are in the high category with a mean of 71% and the highest mean value lies in the category of emotional awareness of 98%.